Conservation Planning and the Development Trajectory of the Historic Core of Worcester, England - Heather Barrett (Urban Planning, 2023)
For over half a century many urban centres in England have been influenced by local conservation policies designed to preserve and enhance their historic townscapes. Whilst these policies have been viewed as broadly successful in preventing the loss of valued historic buildings, there has been limited detailed evaluation of their impact on the localised trajectories of development and change within cities. This article seeks to examine one of these localised trajectories through consideration of the impact of conservation planning on the nature of major development in the commercial core of the historic city of Worcester, England. Utilising local authority planning records, it explores the complex local unfolding of wider conservation and development interests through a focus on the outcomes of planning decision-making evident in the changing nature, location and architectural style of major development in the city core from the late 1980s onwards. The article uses the idea of conservation planning as an “assemblage” to consider how variation in the extent and nature of change across the core reflected the outcome of a complex web of decision-making, moulded by the material agency of a “heritage map” of heritage asset designation. Three distinct “turns” are noted over the study period when shifts in the wider discourses of conservation planning, changing local planning contexts, and amendments to the heritage map produced changes in the local conservation planning assemblage. The discussion highlights how a policy deficiency in articulating the value and significance of the existing urban form and character of the area impacted development proposals and outcomes, leading to the incremental erosion of local character, both in terms of morphological and functional change. The article concludes by reflecting on how exploration of change within local conservation-planning-assemblages might provide insights into some of the current challenges facing urban conservation practice in seeking to articulate how the management of historic urban landscapes can support sustainable urban development.